A Catalogue of the known Species of the World belonging to the Subfamily Aphidiinae (Hymenoptera: Braconidae). - Narayanan, E. S.; Subba Rao, B. R.; Sharma, A. K. (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The above paper contains a catalogue of the known species of the world, belonging to the subfamily Aphidiinae, described up to 1957.